2009
DOI: 10.1111/j.1574-6976.2008.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative approaches for assessing the ecological sustainability ofin situbioremediation

Abstract: Application of microbial metabolic potential (bioremediation) is accepted as an environmentally benign and economical measure for decontamination of polluted environments. Bioremediation methods are generally categorized into ex situ and in situ bioremediation. Although in situ bioremediation methods have been in use for two to three decades, they have not yet yielded the expected results. Their limited success has been attributed to reduced ecological sustainability under environmental conditions. An importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(90 citation statements)
references
References 604 publications
(673 reference statements)
2
81
0
Order By: Relevance
“…Results observed are in accordance with previous reports, which indicate that biodegradable xenobiotic compounds also act as chemoattractants [2,[5][6][7]. Many aromatic acids have been reported to be attractants for Pseudomonas putida PRS2000 [8]. Chemotaxis of Burkholderia sp.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Results observed are in accordance with previous reports, which indicate that biodegradable xenobiotic compounds also act as chemoattractants [2,[5][6][7]. Many aromatic acids have been reported to be attractants for Pseudomonas putida PRS2000 [8]. Chemotaxis of Burkholderia sp.…”
Section: Resultssupporting
confidence: 92%
“…It has been reported that members of the genus Pseudomonas are known to degrade and metabolize a wide variety of xenobiotic compounds and also that they show chemotactic response towards many of these compounds. These include naphthalene [2], chlorinated benzoates and 4-hydroxybenzoate [3,4], methyl parathion and p-nitrophenol [5], benzene, toluene, and trichloroethylene [6], nitro-benzoates and amino-benzoates [7], and aromatic acids [8]. It is believed that chemotaxis plays an important role in metabolism of xenobiotic compounds as it increases the availability of the chemical to the microbe and plays a positive role in metabolism of xenobiotic compounds [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Pseudomonas sp. 1G is reported for biotransformation of imidacloprid (Pandey et al, 2009), Leifsonia sp. (Anhalt et al, 2008).…”
Section: Biodegradation Of Neonicotenoids Pesticidementioning
confidence: 99%
“…Finally, soils treated by bioremediation may be re-used, at least for industrial crops, if acceptable target pollutant levels are reached (Mougin et al, 2009). However, current strategies generally categorized into ex situ and in situ bioremediation have not yet yielded the expected efficiency (Pandey et al, 2009). Fundamental research is needed to reduce cost and to increase performance of bioremediation techniques.…”
Section: Strategies For Bioremediation Of Aromatic Amine-contaminatedmentioning
confidence: 99%